Stable hexacenes through nitrogen substitution - Lindner, Benjamin; Engelhart, Jens U.; Tverskoy, Olena; Appleton, Anthony Lucas; Rominger, Frank; Peters, Anastasia; Himmel, Hans-Jörg; Bunz, Uwe H. F. (Angewandte Chemie. International edition, 2011)
Give me an N: Tetraazahexacenes (see picture, N blue, Si brown) are easily prepared in high yields. Their modular synthesis allows the introduction of any substituent by the choice of suitable quinoxaline derivatives.
Gesehen am 14.09.2022